Control of an underactuated double-pendulum overhead crane using improved model reference command shaping: Design, simulation and experiment - Jaafar H.I.; Mohamed Z.; Ahmad M.A.; Wahab N.A.; Liyana Ramli; Shaheed M.H. (Academic Press, 2024)
Indexed by SCOPUS/ERA